The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.biochi.2018.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of passage number on the impact of the secretome of adipose tissue stem cells on neural survival, neurodifferentiation and axonal growth

Abstract: Mesenchymal stem cells (MSCs), and within them adipose tissue derived stem cells (ASCs), have been shown to have therapeutic effects on central nervous system (CNS) cell populations. Such effects have been mostly attributed to soluble factors, as well as vesicles, present in their secretome. Yet, little is known about the impact that MSC passaging might have in the secretion therapeutic profile. Our aim was to show how human ASCs (hASCs) passage number influences the effect of their secretome in neuronal survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 69 publications
(54 reference statements)
0
17
0
Order By: Relevance
“…The level of secreted IL-6 in some cases was almost at the limit of detection or even beyond, in the other was much higher. Additionally, Serra et al have shown that cellular passaging does not influence significantly ASCs secretome properties [47]. It seems that the donor of the tissue, tissue collection method, and what is more isolation and expansion protocols influence secretion and transcription profile of isolated MSC, causing a difficult issue to compare the results between different laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…The level of secreted IL-6 in some cases was almost at the limit of detection or even beyond, in the other was much higher. Additionally, Serra et al have shown that cellular passaging does not influence significantly ASCs secretome properties [47]. It seems that the donor of the tissue, tissue collection method, and what is more isolation and expansion protocols influence secretion and transcription profile of isolated MSC, causing a difficult issue to compare the results between different laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Our lab has shown that MSC-secretome acts as an important promoter of neuroprotection, neurodifferentiation, by modulating neural stem cells, neurons and glial cells, and axonal growth in vitro and in vivo environments [52,55,56,57,58,59,60,61]. More recently, we have revealed that the use of dynamic culturing conditions (through computer-controlled bioreactors) can further modulate MSC-secretome, generating a more potent neurotrophic factor cocktail [62,63].…”
Section: Mesenchymal Stem Cells (Mscs)-derived Exosomes and Parkinmentioning
confidence: 99%
“…These results show that the presence of WJ-MSCs after the insult is crucial for the improvement of hippocampal cell survival. Importantly, many studies that have assessed the paracrine effects of MSCs have transferred the conditioned medium from MSCs to other cell cultures [ 39 , 40 ]. In the present study, we used a coculture system that allowed the bi-directional interaction between WJ-MSCs and neural cells, without physical contact between the two cell types.…”
Section: Discussionmentioning
confidence: 99%